The ubiquitin proteasome system in glia and its role in neurodegenerative diseases - Jansen, Anne H. P.; Reits, Eric A. J.; Hol, Elly M. (Frontiers in Molecular Neuroscience, 2014)
The ubiquitin proteasome system (UPS) is crucial for intracellular protein homeostasis and for degradation of aberrant and damaged proteins. The accumulation of ubiquitinated proteins is a hallmark of many neurodegenerative diseases, including Amyotrophic lateral sclerosis, Alzheimer’s, Parkinson’s and Huntington’s disease, leading to the hypothesis that proteasomal impairment is contributing to these diseases. So far, most research related to the UPS in neurodegenerative diseases has been focused on neurons, while glial cells have been largely disregarded in this respect. However, glial cells are essential for proper neuronal functioning and adopt a reactive phenotype in neurodegenerative diseases, thereby contributing to an inflammatory response. This process is called reactive gliosis, which in turn affects UPS functioning in glial cells. In many neurodegenerative diseases, mostly neurons show accumulation and aggregation of ubiquitinated proteins, suggesting that glial cells may be better equipped to maintain proper protein homeostasis. During an inflammatory reaction, the immunoproteasome is induced in glia, which may contribute to a more efficient degradation of disease-related proteins. Here we review the role of the UPS in glial cells in various neurodegenerative diseases, and we discuss how studying glial cell functioning might provide essential information in unraveling mechanisms of neurodegenerative diseases.